An unusual presentation of giant molluscum contagiosum diagnosed on cytology. Issue 9 (7th May 2018) - Singh, Smita; Swain, Mitali; Shukla, Shailaja; Chander, Ram
Abstract : Molluscum contagiosum (MC) is most frequently a self‐limiting benign viral skin disease. Transmitted by direct skin contact, it is characterized by flesh‐colored, dome‐shaped, umbilicated lesions. Diagnosis of MC is often done clinically, but when needed, biopsy can be performed, in which characteristic Henderson–Patterson bodies, representing intracytoplasmic assemblies of the virus, are pathognomonic. Atypical presentations of MC are rare in immunocompetent individuals and are challenging to diagnose. We report a case of giant MC, presenting as an ulcero‐proliferative growth, in neck of an 8‐month‐old female child. Fine‐needle aspiration cytology smears revealed characteristic intracytoplasmic molluscum bodies. The diagnosis was subsequently confirmed by histopathology. In this case, cytological examination helped in reaching the correct diagnosis, in a clinically unsuspected case.